3(2y-3)(3y+1)=2(9y-4)(y+1)-7

Simple and best practice solution for 3(2y-3)(3y+1)=2(9y-4)(y+1)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2y-3)(3y+1)=2(9y-4)(y+1)-7 equation:



3(2y-3)(3y+1)=2(9y-4)(y+1)-7
We move all terms to the left:
3(2y-3)(3y+1)-(2(9y-4)(y+1)-7)=0
We multiply parentheses ..
3(+6y^2+2y-9y-3)-(2(9y-4)(y+1)-7)=0
We calculate terms in parentheses: -(2(9y-4)(y+1)-7), so:
2(9y-4)(y+1)-7
We multiply parentheses ..
2(+9y^2+9y-4y-4)-7
We multiply parentheses
18y^2+18y-8y-8-7
We add all the numbers together, and all the variables
18y^2+10y-15
Back to the equation:
-(18y^2+10y-15)
We multiply parentheses
18y^2+6y-27y-(18y^2+10y-15)-9=0
We get rid of parentheses
18y^2-18y^2+6y-27y-10y+15-9=0
We add all the numbers together, and all the variables
-31y+6=0
We move all terms containing y to the left, all other terms to the right
-31y=-6
y=-6/-31
y=6/31

See similar equations:

| 2n+3n-8=4n-7 | | b+1÷-7=2 | | -k-`5k=-5k-4 | | 6x^2−5x+1=0 | | 50=18-a | | 8=-2/9x | | -5x+3+x=19 | | 12x^2+37x-40=0 | | 5+4*x-7=4*x+3-x* | | 4x-2x+3=9x+17 | | 5x-3x+2x=180 | | -2-3/2k=-11/4 | | 3x+6-x=2(x+3) | | 3y5-2y=7+y | | F(x)=2x^2-2x+5 | | 10x12+60=5x12 | | 59+x+x+(x+10)=360 | | 98+2x+5=180 | | -6+2m=-3+3m | | 5x+3x+2x+x=180 | | 2/5x+4/5=2/5 | | 1.82=x-2.3/0.4 | | 13x=117=0 | | 7x+2(3x+16)=-23 | | -2-11/2k=-23/4 | | 5x-3x+2x+x=180 | | 1.10/1+x=0 | | z=8-6/0.5 | | 3q=72;=18 | | 3x-10=6x-22 | | 6x+32=50 | | m/2+10=4 |

Equations solver categories